Designing TALARIA: a New Software to Support Resource Sharing of International Communities - Silvana Mangiaracina (5225537) (2023)
This presentation was given by Silvana Mangiaracina, Alessandro Tugnoli, Debora Mazza, and Rabih Kahaleh, Dario Nobili Library, Bologna Research Area, National Research Council, Bologna, Italy In 2020, the COVID-19 situation forced academic libraries to move exclusively to the Web. To respond to the COVID emergency, in April 2020 a group of librarians under the aegis of IFLA created “Resource Sharing during COVID19” (RSCVD): the first experiment in free digital resource sharingworldwide. RSCVD is based on the voluntary contribution of hundreds of librarians around the world, who worked with the tools available at that moment in order to share documents held in their libraries with the world academic community. After the success of this initiative in the face of the COVID emergency, the Erasmus Plus Programme, through the HERMES project, gives us the opportunity to design a new Resource Sharing software platform for the RSCVD international community. TALARIA software is being designed to support library communities in their resource sharing (RS) management. We aim to build a flexible platform to support different needs and policies of a RS community. Librarians will have access to the RSCVD international community when they have to locate very difficult resources, those RS requests that they are not able to find in their usual collaboration network. For this reason, TALARIA supports the management of difficult requests, allowing users to send a request to all libraries in the community, as well as to a specific library. The software will also support interoperability with other RS management systems, based on the ISO 18626 protocol, in order to connect existing national resource sharing networks.TALARIA will be released as Open Source software, and it will use free Open Source third party software and external services as much as possible.